Selenium levels, selenoenzyme activities and oxidant/antioxidant parameters in H1N1-infected children - Erkekoğlu, Pınar; Aşçı, Ali; Ceyhan, Mehmet; Kızılgün, Murat; Schweizer, Ulrich; Ataş, Can; Kara, Ateş; Koçer Giray, Belma (The Turkish Journal of Pediatrics, 2013)
Selenium (Se) is an essential trace element, and it shows its biological functions within low molecular Se compounds and Se-containing proteins, known as "selenoproteins". Glutathione peroxidases (GPxs) and thioredoxin reductases (TrxRs) are the most important selenoproteins functioning as antioxidant enzymes. These enzymes protect the body from the endogenous products of cellular metabolism that have been implicated in DNA damage, mutagenesis, and carcinogenesis. H1N1 virus is a subtype of the influenza A virus and was an endemic in humans in 2009 and 2010. Taking into account the high incidence of Se deficiency and the high mortality and morbidity rates in H1N1 infection, this study was designed to investigate the plasma and erythrocyte Se levels, selenoenzyme activities and other oxidant/antioxidant parameters in H1N1-infected children during the 2009-2010 pandemic. We observed a significant increase in C-reactive protein levels (245%) and marked decreases in both plasma and erythrocyte Se levels (11%, both) and in GPx1 (45%), GPx3 (16%) and TrxR (30%) activities in H1N1-infected children compared to the control group. In addition, significant decreases were observed in erythrocyte catalase (CAT) (38%), total superoxide dismutase (SOD) (42%) and glutathione S-transferase (GST) (19%) activities and in erythrocyte total glutathione (GSH) (18%) and plasma GSH (10%) concentrations, while marked increases were observed in plasma lipid peroxidation levels (27%). However, we did not find a significant difference in selenoprotein P (SePP) levels between the groups. Our findings show that Se-dependent and -independent blood redox systems are down-regulated in H1N1 influenza. These findings emphasized the critical role of Se as an effective redox regulator and the importance of Se status in infections, particularly in H1N1 influenza.